Cell Cycle-Dependent Turnover of 5-Hydroxymethyl Cytosine in Mouse Embryonic Stem Cells - Otani, Junji (Public Library of Science, 2013)
Hydroxymethylcytosine in the genome is reported to be an intermediate of demethylation. In the present study, we demonstrated that maintenance methyltransferase Dnmt1 scarcely catalyzed hemi-hydroxymethylated DNA and that the hemi-hydroxymethylated DNA was not selectively recognized by the SRA domain of Uhrf1, indicating that hydroxymethylcytosine is diluted in a replication-dependent manner. A high level of 5-hydroxymethylcytosine in mouse embryonic stem cells was produced from the methylcytosine supplied mainly by de novo-type DNA methyltransferases Dnmt3a and Dnmt3b. The promoter regions of the HoxA gene cluster showed a high hydroxymethylation level whilst the methylcytosine level was quite low, suggesting that methylated CpG is actively hydroxylated during proliferation. All the results indicate that removal and production of hydroxymethylcytosine are regulated in replication-dependent manners in mouse embryonic stem cells.